ANALYSIS OF THE CONDITIONS AFFECTING ON THE SAFETY OF FREIGHT CARS WITH COMPUTER SIMULATION METHODS - Cherkashyn, Yu. M.; Lievinzon, M. O.; Mikhalsenko, H. S.; Pohorielov, D. Yu.; Simonov, V. O. (Science and Transport Progress, 2004)
Results of computer modeling of some situations influencing the safety factors of a freight railway vehicle with respect to the derailment are considered. Modeling is performed by means of the Universal Mechanism software with the use of sufficiently detailed models of the freight coach (hopper).